2017
DOI: 10.5511/plantbiotechnology.17.1107a
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel factors that increase enzymatic saccharification efficiency in Arabidopsis wood cells

Abstract: Developing methods to efficiently convert lignocellulosic polymers, i.e. cellulose, hemicellulose, and lignin into user-friendly carbon resources, such as fermentable sugars, is critical for improving plant biomass utilization. Here, we report the identification of genes that increase enzymatic saccharification efficiency in cultured Arabidopsis wood cells. We overexpressed a set of genes that were upregulated during the early stages of in vitro xylem vessel cell differentiation, including transcription factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In this region, BnaA07g26180 corresponding to AT1G02640 was identified as candidate gene, encoding a protein similar to a beta-xylosidase. It was reported that overexpressing this gene could increase enzymatic saccharification efficiency in cultured Arabidopsis wood cells [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this region, BnaA07g26180 corresponding to AT1G02640 was identified as candidate gene, encoding a protein similar to a beta-xylosidase. It was reported that overexpressing this gene could increase enzymatic saccharification efficiency in cultured Arabidopsis wood cells [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our results suggested that only approximately 10% of the selected TF up-regulated during wood formation increased enzymatic saccharification, therefore, the first seedling screening method in this study was effective to find transgenic lines with the improve enzymatic digestibility. In Arabidopsis , a similar approach successfully identified several cell-wall-related TF genes that increase cell wall saccharification efficiency 49 .…”
Section: Discussionmentioning
confidence: 99%
“…The powdered stem samples were treated with a mixture of cellulase from Trichoderma reesei ATCC 26921 (Sigma-Aldrich, Merck KgaA, Darmstadt, Germany) and cellobiase from Aspergillus niger (Sigma-Aldrich, Merck KgaA) for 24 h, according to the methods of Okubo-Kurihara et al (2016) and Ohtani et al (2017b) . The supernatant was collected after centrifugation, after which 0.1 M NaOH solution was added to stop the reaction.…”
Section: Methodsmentioning
confidence: 99%